Influence of surrounding rock temperature on fracture parameters of concrete for shotcrete use in the hot-dry tunnel environments. (26th July 2021) - Cui, Shengai; Cui, Enqi; Xia, Wei; Zeng, Huijiao; Liu, Pin; He, Meng
Highlights: The hot-dry environments with different surrounding rock temperatures were simulated in a laboratory. The fracture performance was tested via a three-point bending test on the notched beams. The fracture toughness and the crack extension resistance of concrete were calculated by the double- K fracture model. Abstract: The objective of this study was to explore the influence of the surrounding rock temperature on fracture parameters of concrete. Four different surrounding rock temperatures were adopted and the three-point bending test on notched beams was conducted in this paper. Based on this test, the fracture energy, initial fracture toughness, unstable fracture toughness, and crack extension resistance of concrete were calculated via the double- K fracture model the KR curve crack propagation criterion. The results are summarized as follows: (1) The fracture energy of concrete beams increased first then decreased with the increment of the hot-dry environment temperature, and reached the peak at 60 °C. (2) The initial fracture toughness, unstable fracture toughness, and crack extension resistance of concrete decreased with the increment of the hot-dry temperature. (3) The length of the fracture process zone increased first then decreased with the increment of the effective crack length.